Comparison of processing routes for efficacious fabrication of Mg3Zn1Ca15Nb biomaterial. Issue 12 (10th September 2021) - Kumar, Ajit; Pandey, Pulak M
ABSTRACT: Different manufacturing techniques unveil their importance to gain advancement in the mechanical, physical, and anti-corrosion properties of Mg-based biomaterial (BM). The present work elucidates the comparative study of mechanical and degradation properties of recently developed novel Mg-based BM viz. Mg3Zn1Ca15Nb fabricated using different manufacturing techniques. The different manufacturing techniques used to fabricate Mg3Zn1Ca15Nb are, namely, conventional sintering (CS), microwave sintering (MWS), and ultrasonic-assisted microwave sintering (UACS). In the very beginning, the aforesaid biomaterial was developed using CS and defended itself as an optimistic biomaterial for orthopedic implants. In the hopes of boosting the obtained properties of developed Mg3Zn1Ca15Nb, MWS and UACS were used later. The experimental results of UACS have shown favorable mechanical as well as degradation properties of Mg3Zn1Ca15Nb. Samples fabricated using all three techniques depicted the presence of only source elements along with substantial dispersion of reinforcement (Nb) within the Mg matrix. All the three manufacturing routes were found compatible for fabricating Mg3Zn1Ca15Nb as no phase constituent was recorded in the X-Ray Diffraction (XRD) analysis. Finally, the cell viability and cytotoxicity assessment were performed for ultrasonic assisted conventionally sintered Mg3Zn1Ca15Nb which exhibited a promising cytocompatibility and better cell attachment characteristics.